Corporate governance reform, board structure and the value relevance of equity book value and earnings in Malaysia / Adibah Jamaluddin - Jamaluddin, Adibah (2006)
This study examines the effect of corporate governance reform and board structure on the value relevance of equity book value and earnings by employing the Ohlson (1995) Valuation Model and based on the methodology developed by Davis-Friday et al. (2006). The sample consists of Main Board companies listed on Bursa Malaysia from 1999 to 2001 in order to investigate the effect during and post the issuance of the Malaysian Code on Corporate Governance (MCCG) as a measure of corporate governance reform. This thesis argues that following the issuance of the Code, companies are better governed and therefore, improves the value relevance of equity book value and earnings reported in the financial statements. Further, if companies comply with the recommendation for best practices contained in the Code, it will be reflected in the increase in the value relevance of equity book value and earnings. The findings generally indicate that equity book value and earnings are value relevant in assisting investors to value firms' equity. Findings of this study, nonetheless, show that the regulatory change experienced by the country did not have an impact on the valuation of equity book value and earnings. Similarly, board composition is found to be statistically insignificant in explaining the association between equity book value and earnings with the firms' value. This, thus, suggests that most of the Malaysian companies may not have met the intended purpose of MCCG, but merely conformed to the minimum requirement. In contrast, mixed results for leadership structure were found where the value relevance of equity book value increase whilst the value relevance of earnings decrease when companies practice duality structure in 2000. It, therefore, implies that the role of CEO and Chairman of the board should be separated in order to improve the value relevance of earnings. In summary, the findings of this study provide evidence that the equity book value and earnings reported in the financial statement is value relevant in valuing Malaysian firms' equity. More importantly, the recommendation by the MCCG to practice unitary leadership structure is deemed vital in improving the value relevance of earnings in Malaysia and hence must be implemented fully.